Murder on the Ballarat train : a Phryne Fisher mystery - Greenwood, Kerry (Greenwood, Kerry. Phryne Fisher mystery., 2006)
When an elderly woman is snatched from her train compartment and murdered, the woman's daughter hires glamorous jazz baby and private investigator Phryne Fisher to find the killers.